A coordinated approach for supply-chain tracking in the liquefied natural gas industry - Wang, J.; Chi, Hung-Lin; Shou, W.; Chong, Heap Yih; Wang, X. (M D P I AG, 2018)
With the increased size and complexity of liquefied natural gas (LNG) projects, supplychain management has become a challenging process due to involvements of the remote location of the project site and the multiple stakeholders. The transparency and traceability of the supply-chain are critical as any surpluses or shortages of materials will put the project at risk. Currently, limited research has been conducted on LNG projects considering the total supply-chain perspective, which refers to all stages of materials tracking in off-site manufacturing, transportation, and site logistics. The purpose of this research is to propose a framework of a coordinated approach for supply-chain tracking in the LNG industry. Two focus group studies were organized to develop the proposed framework: One for LNG construction supply chain process development, and another for alternative tracking technologies selection. In addition, two experiments, namely off-site fabrication tracking and site logistics tracking, were conducted in a field to evaluate the feasibility of the proposed framework. Technology limitations were also discussed in terms of field implementation.